Strategies for Preserving Vision in Secondary Glaucoma Post Congenital Cataract Surgery - Imelda, Eva; Gianty, Jauza Aqilla; Adev, Alya Mutiara; Toshniwal, Navneet Shamsundar (Heca Sentra Analitika, 2023)
Congenital cataract is an eye disorder in the form of impaired lens transparency due to cloudiness that appears at birth or immediately after birth. Post-congenital cataract surgery requires regular monitoring to prevent complications that can reduce visual function. Therefore, this case report aims to describe the incidence of secondary glaucoma in patients with aphakia after congenital cataract surgery with uncontrolled post-operative monitoring regularly. A 4-year-old boy patient was brought by his parents with complaints of reappearance of white spots in the left eye which had become increasingly widespread in the last 2-3 months. Complaints accompanied by a feeling of glare in bright places. The patient's parents said the patient could not focus on seeing objects around him. The patient had a history of congenital cataract surgery in both eyes 2 years ago and did not have routine follow-up after cataract surgery. Congenital cataract is a lens clouding that can occur unilaterally or bilaterally when the child is born or immediately after birth. If monitoring is not carried out routinely, the most common condition that occurs in aphakic after congenital cataract surgery is secondary glaucoma. Regular monitoring after congenital cataract surgery is necessary to achieve successful management and prevent complications.